Nitrogen Recovery With Source Separation of Human Urine—Preliminary Results of Its Fertiliser Potential and Use in Agriculture - Viskari, Eeva-Liisa; Grobler, Gerbrand; Karimäki, Kaisa; Gorbatova, Alexandra; Vilpas, Riikka; Lehtoranta, Suvi (Frontiers in Sustainable Food Systems, 2018)
The growing demand for food and the increasing costs of cultivation are posing a challenge for agriculture. Diminishing phosphorus reserves, as well as the energy intensive method of producing nitrogen fertilisers are drivers for more intensive reuse of different organic fertilisers, such as manures and excreta. Source separation and fertilisation with human urine can be one option for nutrient reuse. Urine contains all the main nutrients as well as micronutrients in soluble form, but it also contains chemicals, like pharmaceuticals and hormones. The aim of this study was to examine the efficiency and safety of the use of source separated human urine as a fertiliser for barley (Hordeum vulgare). The fertiliser efficiency of source-separated urine was examined in field-scale experiments for the first time in Finland. Two separate cultivation experiments in two fields and barley varieties were conducted. The efficiency of urine as a fertiliser was compared to corresponding amount of mineral fertiliser. No fertiliser was applied to one plot in order to create a reference treatment. The two experiments were conducted using variety Wolmari with 54 kg N ha−1 and variety Harbinger with 100 kg N ha−1. The barley grain and straw yield grown with urine fertiliser was equivalent to the yield in mineral fertilised plots. The growth of barley in both fertiliser treatments was slightly faster, compared to non-fertilised treatment. There were no significant differences between the treatments in terms of protein content of the grain although the results varied in terms of the thousand grain weight (TGW) and germination. The urine analyses indicated that there were no pathogen indicators, nor heavy metal concentrations, exceeding the limit values set by legislation. The main nutrient concentrations (N, P, K) would also meet the requirements for a fertiliser product according to Finnish legislation. Pharmaceuticals and hormones were found from the urine, but apart from progesterone, all of them presented extractable values in soil below the detection limits, and they were not detected in measurable amounts in barley grain at the end of the growing season. These results suggest that source separated urine could be an efficient fertiliser in crop cultivation.